STUDY OF TOPONYMS IN HISTORICAL WORKS (AS EXEMPLIFIED BY THE WORK “BABURNAME”) - Davronbek Olimjonov (Western European Studies, 2024)
Zahiriddin Muhammad Babur’s work “Baburname” (“Vaqoyi’”) is considered a historical source across various disciplines, especially in the study of place names. It provides rich information not only for the region of Turkestan but also for Afghanistan and India, making it a valuable resource for examining place names in these areas. Currently, new information related to the historical geography of “Baburname” and different aspects of Babur Mirza’s state is being collected and introduced into scholarly discourse. The results of these toponymic studies undoubtedly contribute to both the preservation and restoration of intangible heritage, enriching the nation’s toponymic gene pool, and advancing research into historical place names to a new theoretical and practical level.
Keywords: Babur Mirza; “Baburname”; toponyms; ethnotoponyms